PENGEMBANGAN MEDIA PEMBELAJARAN TENTANG PEMBUATAN GAMBAR SISIP (INBETWEEN) - Sulistiyono Sulistiyono (Jurnal DutaCom, 2013)
The title of this research is The Development of Learning Media on Making Inbetween with a case study at SMK Negeri 1 Cilacap. The purpose of the research is to meet the requirement to obtain a master degreein computer science which is appropriate aspect of the content, interface and programming. This study only limits on the scope of the Basic Competence Â“ Creating Inline Image (Inbetween) with respondent the Multimedia Class XI at SMK Negeri 1 Cilacap. The research method uses Action Research . Testing in this study is done with the statistical hypothesis of statistic t-test, data retrieval from the control group that is the group without the use of tools and treatment groups that is the group by using the tools. The result of the implementation can illustrated t-table (t critical one-tail) while the value 1.690924255 t-count (t-stat) 32.44752125 value so that it can be interpreted that is a significant difference between the groups that did not the Interactive Learning Media with the group using Media Interactive Learning.